2022
DOI: 10.1108/mip-06-2022-0221
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of augmented reality marketing

Abstract: PurposeAmidst the ambiguity about the impact of augmented reality (AR) attributes on hedonic or utilitarian values, the present study aims to understand what AR attributes create hedonic and utilitarian values and how their interaction determines consumers' behavioral intention.Design/methodology/approachThe study synthesizes the results of 19 quantitative studies on AR marketing by using the meta-analysis technique.FindingsThe findings reveal that interactivity and augmentation are salient AR attributes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…Augmented reality also positively influences utilitarian and hedonic customer value perceptions [30]. A recent meta-analysis confirms utilitarian and hedonic benefits for users' intention to use augmented reality [44]. In consequence, we assume virtual product tests through augmented reality to have a positive impact on price perception.…”
Section: Augmented Reality In Marketingmentioning
confidence: 68%
“…Augmented reality also positively influences utilitarian and hedonic customer value perceptions [30]. A recent meta-analysis confirms utilitarian and hedonic benefits for users' intention to use augmented reality [44]. In consequence, we assume virtual product tests through augmented reality to have a positive impact on price perception.…”
Section: Augmented Reality In Marketingmentioning
confidence: 68%
“…The concept of AR is a significant area for new research in the marketing discipline, as shown through recent literature reviews (e.g., Du et al, 2022; Kumar et al, 2023; Rejeb et al, 2021). Broadly speaking, these studies have focused on defining AR marketing and its characteristics (Hilken et al, 2018; Javornik, 2016; Rauschnabel, Felix, et al, 2022) or assessed strategic (Hilken, Chylinski, et al, 2022; Javornik, Duffy, et al, 2021; Rauschnabel, Babin, et al, 2022) and consumer‐related (e.g., Kumar et al, 2023; Sung et al, 2021; tom Dieck & Han, 2022) research questions. Overall, prior research finds that consumers typically perceive AR content as useful (Gatter et al, 2022) and inspirational (Arghashi, 2022; Rauschnabel et al, 2019; Zanger et al, 2022).…”
Section: Theory and Prior Researchmentioning
confidence: 99%
“…The mix of benefits and challenges associated with AR may explain consumer hesitance in adopting these technologies. Nevertheless, consumer benefits currently appear to outweigh these drawbacks, and research has identified a number of positive outcomes of AR marketing, such as brand perception (Rauschnabel et al, 2019; Zanger et al, 2022), purchase intention (Zanger et al, 2022), sales (Tan et al, 2022), customer satisfaction (Dacko, 2017), loyalty (Dacko, 2017), and a willingness to pay (Heller et al, 2019a; for a review, see Du et al, 2022; and Kumar et al, 2023).…”
Section: Theory and Prior Researchmentioning
confidence: 99%
“…Furthermore, the metaverse can be a place to live out one's dreams with a new appearance, identity, activity, space, and others. Such social values in the metaverse exert psychological and behavioral influences, such as increases in self‐efficacy and hedonic values (Kumar et al, 2023; Oh et al, 2023; Ying et al, 2022), evidencing the significance of social metaverse. Considering that people satisfy social needs through virtual interaction and relationships, the role of the metaverse on consumer's psychology and behavior should be further identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interaction helps metaverse users to develop a virtual relationship and construct a virtual society. Hence, the level of interaction further increases user values and intentions (Kumar et al, 2023). Finally, the metaverse adds social value to society as a tool.…”
Section: Literature Reviewmentioning
confidence: 99%